A reproducible sensor pattern to suspect COVID19 pulmonary infection with LATITUDE. Case report and literature review. Issue 3 (23rd February 2022) - Zanchi, Simone; La Greca, Carmelo; Di Nanni, Nunzia; Fogliata, Emma; Zani, Mariangela; Pecora, Domenico
Abstract: A 78 year‐old patient with postischaemic dilated cardiomyopathy and severely reduced ejection fraction was implanted with a Boston Scientific RESONATE X4 CRT‐D and followed by LATITUDE remote monitoring platform. From the end of January to the end of March 2021 he was hospitalized for COVID19 pneumonia followed by two episodes of acute heart decompensation with bilateral pleural effusion. We remotely followed the patient and identified a typical Heart Logic sensor pattern linked to the COVID19 pneumonia, different from the one linked to the heart failure (HF). We eventually made a literature review on the topic.